A longitudinal study of the effects of teaching motivational strategies to adolescents from a self-determination theory perspective - Sewell, Y (2022)
This study investigated the effects of an intervention program on motivation and English language proficiency amongst English language learners at a middle school in China. Twenty-three grade 7 (11-13-year-olds) were randomly assigned to either the treatment or the control group. The treatment group were explicitly taught the motivated learning strategy of goal setting (goal setting group), while the control (or normal teaching group) received English instruction as usual. The intervention lasted for 18 weeks, wherein students were taught about goal setting, set goals and actions to achieve them, and reflected on them weekly. The evaluation of the effectiveness of the intervention included data from pre and posttest motivation questionnaires, and standard test results for reading and language use, as per the school’s requirement, from two data points (pre and posttest). The results of the immediate training effects of goal setting on motivation and English proficiency were promising, despite being statistically non-significant. The feature of the current study design allowed for an exploration of the possibility of manipulating motivation through goal setting and the possible effect on language achievement.